Implementation of an Adsorption Model in EMSO Software for Ethanol-Water Mixture Separation - L. Stinguel; M.R. Wolf-Maciel; R. Guirardello (Chemical Engineering Transactions, 2016)
The main form of bioethanol production is fermentation of sugar cane juice which is proven to be the best raw material for bioethanol production. A major problem in ethanol production is the high energy cost associated with their separation because of water excess and the existence of an azeotrope in the ethanol-water mixture which through the conventional distillation can be separated to a maximum of 95% by weight. In order to produce anhydrous ethanol another distillation type is required, called dehydration, which the most used are the azeotropic and extractive distillation. However the production by adsorption has increased greatly in recent years because of the need for a purer product. Although the adsorption project to separate ethanol from water is very laborious as it must operate in cycles, this leads to the use of simulation as an outlet for the design of an adsorption process. Among the simulators available in the market there is EMSO (Environment of Modeling, Simulation and Optimization), which is an easily accessible and free simulator, but EMSO has no adsorption model in its library. Thus the main objective of this work is the implementation of an adsorption model in EMSO software to separate the ethanol-water mixture. The mathematical model used in this study was taken from the literature, which was used for ethanol dehydration in a complete adsorption cycle. This simplified model is based on material balance and the variation of the superficial velocity of the fluid equations. The adsorption simulations were performed with the total time of 345s, as this is the time taken for a column to be saturated in an adsorption cycle. The water mole fraction profile satisfactorily in the simulations, which leads to the conclusion that the EMSO software may well be used for the simulation of a process of separation of ethanol-water mixture by adsorption has been reached.